A child called "it" : one child's courage to survive - Pelzer, David J. (Child called "It" series, 1995)
A Child Called "It" is an account of one of the most severe child abuse cases in California history. It is the story of Dave Pelzer, who was brutally beaten and starved by his emotionally unstable, alcoholic mother: a mother who played torturous, unpredictable games - games that left him nearly dead. He had to learn how to play his mother's games in order to survive because she no longer considered him a son, but a slave; and no longer a boy, but an "it."--